2010
DOI: 10.1093/jb/mvq138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of recombinant protein expression in a baculovirus system in insect cells (Sf9) and silkworm

Abstract: Using a hybrid baculovirus system, we compared the expression of 45 recombinant proteins from six categories using two models: silkworm (larvae and pupae) and an Sf9 cell line. A total of 45 proteins were successfully expressed; preparation of hybrid baculovirus was unsuccessful for one protein, and two proteins were not expressed. A similar pattern of expression was seen in both silkworm and Sf9 cells, with double and multiple bands found in immunoblotting of the precipitate of both hosts. Degraded proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The predominant MW of 24 kDa corresponds to paucimannose structures, according to bioinformatic analysis and previous works (Kulakosky et al 1998). Multiple bands due to glycosylation have previously described by other authors with the expression of recombinant IFN in insect cells and Bombyx mori larvae (Na et al 2008;Usami et al 2011). In this case, the biological activity of the rFeIFNβ was not altered by this glycosylation heterogenicity.…”
Section: Deglycosylationsupporting
confidence: 64%
“…The predominant MW of 24 kDa corresponds to paucimannose structures, according to bioinformatic analysis and previous works (Kulakosky et al 1998). Multiple bands due to glycosylation have previously described by other authors with the expression of recombinant IFN in insect cells and Bombyx mori larvae (Na et al 2008;Usami et al 2011). In this case, the biological activity of the rFeIFNβ was not altered by this glycosylation heterogenicity.…”
Section: Deglycosylationsupporting
confidence: 64%
“…Significantly, the commercially available VLP-based vaccine, Cervarix™, was also produced in the Tn5 cells [141]. Additionally, one research group demonstrated that the silkworm could produce higher levels of recombinant proteins than Sf9 cells, although the level of expression of soluble protein was higher in Sf9 cells than in the silkworm for all proteins except the membrane proteins [142]. These differences most likely reflect the great level of complexity of the biological systems in silkworms, compared with that in Sf9 cells.…”
Section: Host Factorsmentioning
confidence: 99%
“…This system is remarkably efficient. Many experiments have shown that the expression level of a heterologous protein in five silkworm larvae or pupae is approximately equal to the expression levels of fermentation products from 1 L of sf9- Ac MNPV cells [ 7 ]. Therefore, this reBmBac-silkworm expression system is a rapid and highly efficient system for producing large amounts of foreign protein.…”
Section: Discussionmentioning
confidence: 99%
“…Autographa californica nucleopolyhedrovirus ( Ac MNPV)-Sf9 and Bombyx mori nucleopolyhedrovirus ( Bm NPV)-silkworm are two typical BEVSs [ 4 – 6 ]. The Bm NPV-silkworm offers several advantages in comparison with the Ac MNPV-Sf9 system [ 7 ].…”
Section: Introductionmentioning
confidence: 99%